Working Capital Management and Bank Performance of Nepalese Commercial Banks - Shrestha, Bismita (Nepalese Journal of Finance, 2024)
This study examines the relationship between working capital management and bank performance of Nepalese commercial bank. Return on assets and return on equity are selected as the dependent variables. Similarly, working capital, bank size, leverage, liquidity ratio, capital adequacy ratio, non-performing loan, credit to deposit ratio and operational efficiency ratio are selected as the independent variables. This study is based on secondary data of 15 commercial banks with 105 observations for the study period from 2015/16 to 2021/22. The data were collected from Banking and Financial statistics published by Nepal Rastra Bank, reports published by Ministry of Finance, and annual report of respective banks. The correlation coefficients and regression models are estimated to test the significance and importance of working capital management on the performance of Nepalese commercial banks. The study showed that working capital, bank size, liquidity ratio and capital adequacy ratio have a positive impact with return on assets. It indicates that increase in working capital, bank size, liquidity ratio and capital adequacy ratio leads to increase the return on assets. However, leverage, non-performing loan, credit to deposit ratio and operational efficiency ratio have a negative impact with return on assets. It indicates that increase in leverage, non-performing loan, credit to deposit ratio and operational efficiency ratio leads to decrease the return on assets. On the other hand, the study also showed that working capital, bank size, liquidity ratio and capital adequacy ratio have a positive impact with return on equity. It indicates that increase in working capital, bank size, liquidity ratio and capital adequacy ratio leads to increase the return on equity. However, leverage, non-performing loan, credit to deposit ratio and operational efficiency ratio have a negative impact with return on equity. It indicates that increase in leverage, non-performing loan, credit to deposit ratio and operational efficiency ratio leads to decrease the return on equity.